Thermo-Rheological Properties of the Ethiopian Lithosphere and Evidence for Transient Fluid Induced Lower Crustal Seismicity Beneath the Ethiopian Rift - Muluneh, Ameha A.; Keir, Derek; Corti, Giacomo (Frontiers in Earth Science, 2021)
Lower crustal seismicity in the volcanically active Main Ethiopian Rift (MER) and north-western (NW) plateau is observed at depths where the temperature is expected to be too high for brittle failure to occur. Here we use the available earthquake catalogues and compute theoretical predictions for a range of conditions for the occurrence of lower crustal earthquakes beneath the MER and adjacent northwestern plateau. Yield strength envelops are constructed using information on geothermal gradient, strain rate and composition constrained by geophysical observations. Our models suggest that away from the MER beneath the NW plateau the depth distribution of earthquakes in the lower crust is best explained by strong mafic lower crustal rheology and hydrostatic fluid pore pressure conditions. In the same region the effective elastic thickness is similar to seismogenic thickness showing that the lower crust has long-term strength and hence can sustain brittle deformation. On the contrary, in the central MER the seismogenic thickness is much larger than the effective elastic layer thickness implying that the lower crust has no long-term strength. Here our models show that both hydrostatic and near-lithostatic fluid pore pressures fail to explain the observed seismicity and instead high pore fluid pressure and transient strain rate due to the movement of fluids provide a plausible mechanism for the occurrence of seismicity in the lower crust. Our interpretations are supported by occurrence of swarms of deep earthquakes beneath the MER, as opposed to more continuous background deep seismicity away from the rift. Using time-depth progression of earthquakes, we estimate permeability values of 5.9×10^−15 m^2 and 1.8×10^−14 m^2 at lower crustal depth. The range of permeability implies that seismicity can be induced by pore-pressure diffusion, likely from fluids sourced from the mantle that reactivates preexisting faults in the lower crust. Our thermo-rheological models explain the first order differences in lower crustal earthquakes both directly beneath and outboard of the rift valley.